(untitled) (Research, Society and Development, 2025)
Corn is often grown as a second crop under unsuitable conditions for its full development, and it is essential to maintain productivity even in adverse situations. The objective of this study was to verify whether inoculation with Bacillus aryabhattai and topdressing applications on the soil surface provide increased productivity in corn crops. In all treatments, the plants were inoculated with 4.0 ml of B. aryabhattai (TS). In T2 and T3, an additional 100 ml ha-1 was applied at V4, and later in T3 and T4, an additional 100 ml ha-1 was applied at V8 stage. The plants were analyzed by assessing height (m) and stem diameter (mm) and productivity. The results of the evaluations were subjected to analysis of variance, and when significant differences occurred, Tukey’s test of means was applied. The application of B. aryabhattai promotes the best development of corn plants. The association of B. aryabhattai applied in seed treatment, and in V4 of corn, promotes significant benefits for crop productivity.